Arsenic enriched groundwater discharge to a tropical ocean: Understanding controls and processes. (1st February 2023) - Coomar, Poulomee; Das, Kousik; Debnath, Palash; Verma, Swati; Das, Prerona; Biswas, Ashis; Mukherjee, Abhijit
Abstract: The role of submarine groundwater discharge (SGD) in transporting terrestrial-sourced arsenic (As) to the global oceans is not well documented. In the present study, executed on a coast adjoining the extensive groundwater As-contaminated Ganges river delta, we hypothesize that As-enriched groundwater discharges to the adjoining Bay of Bengal (BoB) through SGD flow paths. We conducted high-resolution, field-based investigations and thermodynamic modeling to understand the SGD-sourced As discharge and geochemical cycling of As and other redox-sensitive solutes along the discharge path under varying redox conditions and water sediment interactions. The As distribution and other solutes were measured in a series of multi-depth observation wells and sediment cores, extending from the high tide line (HTL) to 100 m toward the sea, for pre- and post-monsoon seasons. Results reveal the presence of a plume carrying up to 30 μg/L dissolved load of As toward the sea. Arsenic is associated with a plume of Fe and exhibits similar shore-perpendicular variability. Arsenic distribution and transport is controlled by the Fe-Mn redox cycle and influenced by terrestrial groundwater discharge. Field-observations and geochemical modeling demonstrate that Fe-hydroxide precipitates in the subterranean estuary and acts as an interim sink for As, which is eventually mobilized on alteration of geochemical conditions with the season. Fluctuating plume size can be attributed to seasonal variation in fresh groundwater input to the site. Estimates indicate up to 55mg/m 2 /d As is released to BoB from the site. Based on physicochemical observations this study demonstrates the yet to be studied SGD derived As cycles and the role of SGD dynamics in controlling the fate of redox-sensitive contaminants and their discharge into global oceans. Graphical abstract: Image 1 Highlights: Submarine groundwater discharge mediated As transport is documented at a tropical coast. Discharge zone is characterized by precipitates of Fe, Mn-(oxy)hydroxides. Arsenic release is modulated by fresh groundwater flux at the site. Up to 55 mg/m 2 /d of As is released to the sea. Seasonally varying freshwater flux controls the degree of As release.